PENGARUH KECERDASAN EMOSI DAN SELF EFFICACY TERHADAP PRODUKTIVITAS KERJA MELALUI MOTIVASI KERJA (STUDY PADA KARYAWAN RUMAH SAKIT IBU DAN ANAK BINA MEDIKA) - Heni Suhaeni; Agus Fauzi; Sitorus, Guston (Pasca Sarjana Universitas Satya Negara Indonesia, 2022)
This study aims to determine the effect of the variable emotional intelligence and self-efficacy partially or simultaneously on work productivity through work motivation. The population of this study using random sampling is all employees of RSIA Bina Medika taken randomly. The sample data used are 147 samples from 223 employees. The research design is quantitative research. The method of data collection in this research is to conduct surveys and distribute questionnaires using digital forms. In addition, there are several methods of data analysis in this study, namely descriptive analysis, classical assumption test, multiple linear regression test and path analysis test. The types of data used in this study are primary and secondary data. The results of the simultaneous and partial test prove that the variables of emotional intelligence and self-efficacy on work productivity through work motivation have an effect on each other. This is evidenced by the F test obtained that the calculated F value is 4.330 with a significant level of 0.001 which is smaller than alpha 0.05 (5%). The calculated F produced is 4.330, which is greater than the F table, which is 3.06. Thus, simultaneously emotional intelligence and self-efficacy have a positive and significant effect on work motivation. Thus, simultaneously emotional intelligence, self-efficacy, and work motivation have a positive and significant effect on work productivity.